2018
DOI: 10.1016/j.jchromb.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical flow field-flow fractionation in purification of an enveloped bacteriophage ϕ6

Abstract: Basic and applied virus research requires specimens that are purified to high homogeneity. Thus, there is much interest in the efficient production and purification of viruses and their subassemblies. Advances in the production steps have shifted the bottle neck of the process to the purification. Nonetheless, the development of purification techniques for different viruses is challenging due to the complex biological nature of the infected cell cultures as well as the biophysical and -chemical differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…The retention times at the peak maxima varied from ~28 min to 29.5 min between experiments that were performed with different virus batches and on different dates ( Figure S3A, Supplementary Materials ). Our recent AF4-multi-angle light-scattering measurement (MALS) study showed that ultracentrifugation-based purification of φ6 yields virus specimen that has a relatively homogenous size distribution and little aggregates [ 5 ]. Virus-sized particles are generally well retained in the AF4 channel and elute at low cross-flow rates [ 5 , 38 , 39 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The retention times at the peak maxima varied from ~28 min to 29.5 min between experiments that were performed with different virus batches and on different dates ( Figure S3A, Supplementary Materials ). Our recent AF4-multi-angle light-scattering measurement (MALS) study showed that ultracentrifugation-based purification of φ6 yields virus specimen that has a relatively homogenous size distribution and little aggregates [ 5 ]. Virus-sized particles are generally well retained in the AF4 channel and elute at low cross-flow rates [ 5 , 38 , 39 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our recent AF4-multi-angle light-scattering measurement (MALS) study showed that ultracentrifugation-based purification of φ6 yields virus specimen that has a relatively homogenous size distribution and little aggregates [ 5 ]. Virus-sized particles are generally well retained in the AF4 channel and elute at low cross-flow rates [ 5 , 38 , 39 , 45 ]. When compared to our previous study on φ6 that was performed with a thicker 350 μm spacer and resulted in virus elution at the end of the cross-flow gradient [ 5 ], here the thinner spacer promoted virus elution at higher cross-flow rates (peak maxima at a cross-flow rate of ~0.25 mL/min), providing improved resolution between monomeric viruses and putative larger sample components that are present if purification is performed with less purified inputs such as lysates or virus precipitates [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations